Carcinogen Metabolism Pathway and Tumor Suppressor Gene Polymorphisms and Gallbladder Cancer Risk in North Indians: A Hospital-Based Case-Control Study - Asai, Takao (Asian Pac J Cancer Prev, 2019)
BACKGROUND: Carcinogen metabolism pathway and tumor suppressor gene polymorphisms have been reported to be associated with increased gallbladder cancer risk. However, the association of genetic variants and gallbladder cancer risk in Indians are not well studied. We examined whether genetic polymorphisms of metabolic enzymes cytochrome P450 1A1 and glutathione S-transferase and tumor suppressor gene p53 (TP53) are associated with an increased risk of gallbladder cancer in North Indians. METHODS: This hospital-based case-control study was conducted in 96 gallbladder cancer patients with gallstones (cases) and 93 cholelithiasis patients (controls) at the Sanjay Gandhi Postgraduate Institute of Medical Sciences in Lucknow, India from July 2014 through May 2017. Genomic DNA was extracted from white blood cells of each patient using a simple salting-out procedure. The genotypic frequencies of CYP1A1 rs4646903, CYP1A1 rs1048943, and TP53 rs1042522 polymorphisms were investigated using TaqMan SNP Genotyping Assay and GSTM1 and GSTT1 polymorphisms were analyzed using the multiplex PCR assay. RESULTS: The frequency of CC genotype of TP53 rs1042522 polymorphism was 27.1% (26/96) in cases and 12.9% (12/93) in controls. The CC genotype was associated with an increased risk of gallbladder cancer in North Indians (age- and sex-adjusted odds ratio, 2.81; 95% confidence interval, 1.19–6.61; P = 0.02). No significant differences in genotypic and allelic frequencies of the metabolic pathway gene polymorphisms were found between cases and controls. CONCLUSIONS: Our data provide preliminary evidence that the CC genotype of the TP53 rs1042522 polymorphism may be associated with an increased risk of gallbladder cancer in North Indians.